The Big data analysis on historical tweets on Indonesian Heroes' day - Zudan Rosyidi; Rahma Sugihartati; Septi Ariadi (Jurnal Studi Komunikasi, 2023)
The changes in the historical text on Twitter are starting point of this research. The moment of the Heroes' Day commemoration on Twitter becomes the entry point to analyse these changes. Therefore, this study analyses historical text tweets at that moment by paying attention to the context surrounding the users. The study uses a content analysis method, emphasising a qualitative approach. Two data collection techniques are used to obtain accurate and faster details: manual observation and data crawling by Python program. This study found three dominant text variations. The first is a text containing a narrative about Bung Tomo, public information about the Hero, and the word "ex" (mantan -Indonesian) to commemorate users' relations. There are ten dominant words used in the three variations of the text.